2019
DOI: 10.5624/isd.2019.49.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional comparison of 2 digital models obtained from cone-beam computed tomographic scans of polyvinyl siloxane impressions and plaster models

Abstract: Purpose: This study was performed to evaluate the dimensional accuracy of digital dental models constructed from conebeam computed tomographic (CBCT) scans of polyvinyl siloxane (PVS) impressions and cast scan models. Materials and Methods: A pair of PVS impressions was obtained from 20 subjects and scanned using CBCT (resolution, 0.1 mm). A cast scan model was constructed by scanning the gypsum model using a model scanner. After reconstruction of the digital models, the mesiodistal width of each tooth, interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 20 publications
1
16
2
2
Order By: Relevance
“…To the best of our knowledge, the current research was one of the few studies to be conducted in vivo to compare between these two techniques of virtual models fabrication (12,15,16). Generally, in a systematic review (17,18) it was proved that the mean differences between linear measures on stone and virtual models are within this range (0.04-0.4 mm) and considered it accepted clinically.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To the best of our knowledge, the current research was one of the few studies to be conducted in vivo to compare between these two techniques of virtual models fabrication (12,15,16). Generally, in a systematic review (17,18) it was proved that the mean differences between linear measures on stone and virtual models are within this range (0.04-0.4 mm) and considered it accepted clinically.…”
Section: Discussionmentioning
confidence: 96%
“…Thereby, digital model production using CBCT scans of patient impressions and casts is an alternative method to intraoral scanner or a desktop scanner without the need for directly irradiating the patient. Moreover, single impression can be used for both virtual and stone models fabrication if needed (12,13). Of particular interest is the reliability and accuracy of some of these newer techniques and their applications in-vivo in relation to well established methods, such as conventional stone casts as the previous studies were conducted mainly in-vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Our results concerning the analysis of CBCT scans are also in line with those reported in the literature, not as much for scanning models but for scanning dental impressions [ 1 ]. Park et al reported the accuracy of CBCT in scanning impressions and compared it to measurements made on plaster dental models [ 27 ]. The average difference in this study was 0.15 mm, which was also considered clinically acceptable; this result coincides with the result of our study—a median difference of 0.14 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoral scanners (IOS) are used in dentistry as a convenient method of taking impressions [ 1 , 2 , 3 , 4 , 5 , 6 ]. Orthodontic tooth movement can also be easily evaluated using IOS [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%